PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus esculentus L. Moench) DI KABUPATEN REJANG LEBONG - Kiky Nurfitri Sari; Andika Prawanto; Ria Oktanina Purba (University of Prof. Dr. Hazairin, SH, 2021)
This study aims to determine the growth and yield of Okra plants in the highlands of Rejang Lebong Regency. This research was conducted at the Simpang Nangka Experimental Garden, Selupu Rejang District, Rejang Lebong Regency. The experimental design used in this study was a completely randomized design (CRD) with p lant genotype treatment, namely G1 (Green Okra) and G2 (Red Okra). Each treatment consisted of ten plant samples which were repeated three times so that there were 60 plant samples. In this study, observations were made on quantitative observational variables. The quantitative observation variables consisted of plant height, number of leaves, length of crates, diameter of crates, number of books, stem diameter, flowering age, number of fruit planted, fruit weight, fruit length, fruit diameter. The results showed that there was a tendency that red varieties were able to produce superior vegetative and generative components.